Chapter The Tools of War in the Cancellieri Vendetta - Szolnoki, Zoltán (Wydawnictwo Uniwersytetu Łódzkiego, 2025)
The Cancellieri vendetta, a conflict between members of the Cancellieri clan, took place in the 13th century, perhaps in the year 1300. In terms of narrative sources, we can identify two distinct groups of records: the Florentine tradition and the Pistoia chronicle. The vendetta determined the history of both Pistoia and the Tuscan region, as the antagonisms among the Pistoiain elite caused similar factional strife in Florence as well when the leaders of the two Cancellieri factions moved to the nearby city. The so-called ‘White’ Cancellieri were linked with the Florentine White Guelphs; the other party were linked with the Florentine Black Guelphs. The leaders of the Florentine factions – the Donati (Blacks) and the Cerchi (Whites) – were opponents in everyday politics. The impulse of the Cancellieri clan members had a huge effect on the situation leading to violent factional wars in Florence that ended in 1308. In my study, I analyse the narrative sources of this period, both from Pistoia and from Florence, and examine the tools used in the fights: the ‘tangible’ weapons that were mentioned by the anonymous writer from Pistoia and the ‘narrative’ tools of the Florentine tradition.